Workplace spirituality as a moderator in the relationship between soft TQM and organizational commitment - Adawiyah, Wiwiek Rabiatul; Mohd Shariff, Mohd Noor; Saud, Mohammad Basir; Mohd Mokhtar, Sany Sanuri (Centre for Promoting Ideas, 2011)
This study examined the moderating effects of workplace spirituality on the relationship between soft TQM and organizational commitment on Islamic banks in Central Java, Indonesia. The study was dependent on a survey conducted on 850 employees of Islamic banks using a random sampling technique.The tool of analysis used in this study was hierarchical regression analysis.The finding of the study showed that all Soft TQM dimensions, except education and training, have positive and significant influence on organizational commitment.Moreover workplace spiritual values appear to moderate empowerment and organizational commitment associations as well as customer focus linkage with employees’ commitment towards Islamic banks. Based on the findings, implications to practice are offered.